Etiological surveillance of viral diarrhea from 2017 to 2019 in Zhangzhou city, Fujian province, China - Guo, Yueli; Chen, Weide; Wang, Guowei; Yang, Huicong; Zhou, Qiaoling; Zhang, Chunbin; Zeng, Yuanjun (Frontiers in Public Health, 2024)
Background: Viral diarrhea is one of the major causes of morbidity and mortality in children. This study aimed to conduct etiological surveillance of viral diarrhea in Zhangzhou city, Fujian Province, China, from 2017-2019 to identify the prevalence, distribution, and characteristics of viral pathogens causing gastrointestinal infections in the region.Methods: Stool samples were collected from patients with acute diarrhea in Zhangzhou City, Fujian Province, China, from 2017-2019. Rotavirus, norovirus, astrovirus and adenovirus were detected using fluorescence immunochromatography assay.Results: Of the total 5627 samples that were collected, at least one of the viruses (rotavirus, norovirus, astrovirus and adenovirus) was found to be positive in 1422 samples. Rotavirus, norovirus, astrovirus and adenovirus, were detected in 53.73%, 16.68%, 15.52% and 14.97%, respectively.Mixed infections were determined in 17.65% of the positive samples. The predominant mixed infections observed were a combination of norovirus and astrovirus, followed by rotavirus and norovirus, and rotavirus and astrovirus. The highest positive rate was observed in the 12-23-month group for rotavirus and adenovirus, while a significantly higher positive rate was observed for norovirus and astrovirus in the 6-11-month group. Conclusion: These findings from this etiological surveillance highlight the significant burden of viral diarrhea in Zhangzhou City, with rotavirus being the predominant pathogen. The identification of common mixed infections provides insights into the complex nature of viral diarrhea transmission.Target interventions and public health strategies should be implemented, particularly during the winter and spring seasons, to prevent and control the spread of viral pathogens causing gastrointestinal infections in this region.